Climate drove the fire cycle and humans influenced fire occurrence in the East European boreal forest. Issue 4 (30th June 2022) - Ryzhkova, N.; Kryshen, A.; Niklasson, M.; Pinto, G.; Aleinikov, A.; Kutyavin, I.; Bergeron, Y.; Ali, Adam A.; Drobyshev, I.
Abstract: Understanding long‐term forest fire histories of boreal landscapes is instrumental for parameterizing climate–fire interactions and the role of humans affecting natural fire regimes. The eastern sections of the European boreal zone currently lack a network of annually resolved and centuries‐long forest fire histories. To fill in this knowledge gap, we dendrochronologically reconstructed the 600‐year fire history of a middle boreal pine‐dominated landscape of the southern part of the Republic of Komi, Russia. We combined the reconstruction of fire cycle (FC) and fire occurrence with the data on the village establishment and climate proxies and discussed the relative contribution of climate versus human land use in shaping historic fire regimes. Over the 1340–1610 ce period, the territory had a FC of 66 years (with the 90% confidence envelope of 56.8 and 78.6 years). Fire activity increased during the 1620–1730 ce period, with the FC reaching 32 years (31.0–34.7 years). Between 1740–1950, the FC increased to 47 years (41.9–52.0). The most recent period, 1960–2010, marks FC's historic maximum, with the mean of 153 years (102.5–270.3). Establishment of the villages, often as small harbors on the Pechora River, was associated with a non‐significant increase in fire occurrence in the sites nearest the villages ( p  = 0.07–0.20). We, however, observed a temporal association between village establishment and fire occurrence at the scale of the whole studied landscape. There was no positive association between the former and the FC. In fact, we documented a decline in the area burned, following the wave of village establishment during the second half of the 1600s and the first half of the 1700s. The lack of association between the dynamics of FC and the dates of village establishments, and the significant association between large fire years and the early and latewood pine chronologies, used as historic drought proxy, indirectly suggests that the climate was the primary control of the landscape‐level FCs in the studied forests. Pine‐dominated forests of the Komi Republic may hold a unique position as the ecosystem with the shortest history of human‐related shifts in fire cycles across the European boreal region.